KOMUNIKASI ANTAR IMPLEMENTOR KEBIJAKAN PENEMPATAN DAN PEMANFAATAN TENAGA KERJA LOKAL DI KABUPATEN PELALAWAN - Insani Santa Maria; Hasim As'ari (Journal Publicuho, 2022)
Labor problems are one of the problems in Pelalawan Regency that have not been well resolved to date, such as the placement of local workers which has not been carried out optimally by various companies. The purpose of this study was to determine the communication policy on the placement and utilization of local workers implemented by the company to minimize or reduce the unemployment rate in Pelalawan Regency. This type of research is descriptive qualitative and the data needed are primary data and secondary data derived from observations, interviews and documentation which were analyzed by researchers so as to obtain accurate and clear data regarding the communication of policies on placement and utilization of local workers in Pelalawan Regency. The results of this study conclude that communication between the policy implementors of the placement and utilization of local workers in Pelalawan Regency is not in accordance with the communication indicators according to Edwards. The transmission of policies on the placement and utilization of local workers by the Pelalawan Regency Manpower Office to companies is still ineffective, so that companies are inconsistent in absorbing local workers and companies do not provide information on job vacancies to the Pelalawan Regency Manpower Office